2020
DOI: 10.1002/ejoc.202000221
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Phosphonium Salts from Phosphines and Carbenium: Efficient CO2 Fixation and Phase‐Transfer Catalysts

Abstract: A new library of phosphonium salts has been synthesized from the reaction of tris-(2,6-dimethoxyphenyl)carbenium with different phosphines. The resultant phosphoninum salts work as efficient phase-transfer catalysts for the alkylation of 1,3-dicarbonyl compounds. One compound, a bifunctional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This is the first example of the recycling of a plasma‐immobilized catalyst, although the yields gradually decreased after the second run [32] . Gianetti's group developed the bifunctional phosphonium salt 53 , prepared from tris‐(2,6‐dimethoxyphenyl)‐carbenium and an aminophosphine, for CO 2 fixation reactions with epoxides under mild conditions [33] . The catalyst 53 also acted as an efficient phase‐transfer catalyst for the alkylation of 1,3‐dicarbonyl compounds 54 (Scheme 16).…”
Section: Annulation Reactions: [2+1] [2+1+1] [3+2] [4+1] and [4+2mentioning
confidence: 99%
“…This is the first example of the recycling of a plasma‐immobilized catalyst, although the yields gradually decreased after the second run [32] . Gianetti's group developed the bifunctional phosphonium salt 53 , prepared from tris‐(2,6‐dimethoxyphenyl)‐carbenium and an aminophosphine, for CO 2 fixation reactions with epoxides under mild conditions [33] . The catalyst 53 also acted as an efficient phase‐transfer catalyst for the alkylation of 1,3‐dicarbonyl compounds 54 (Scheme 16).…”
Section: Annulation Reactions: [2+1] [2+1+1] [3+2] [4+1] and [4+2mentioning
confidence: 99%
“…[ 14] Our group has recently reported that phosphines react in a similar manner, even with the more electron-rich hexametoxytriphenyl-carbenium ion. [15] Interestingly, trioxatriangulenium ion (TOTA + , Figure 1b), the heterocyclic fused analog of hexametoxytriphenyl-carbenium ion, first reported by Smith et. al.…”
mentioning
confidence: 95%